Effects of Skin Thickness on Cochlear Input Signal Using Transcutaneous Bone Conduction Implants. Issue 8 (September 2015) - Mattingly, Jameson K.; Greene, Nathaniel T.; Jenkins, Herman A.; Tollin, Daniel J.; Easter, James R.; Cass, Stephen P.
Abstract : Hypothesis: Intracochlear sound pressures ( P IC ) and velocity measurements of the stapes, round window, and promontory ( V Stap/RW/Prom ) will show frequency-dependent attenuation using magnet-based transcutaneous bone conduction implants (TCBCIs) in comparison with direct-connect skin-penetrating implants (DCBCIs). Background: TCBCIs have recently been introduced as alternatives to DCBCIs. Clinical studies have demonstrated elevated high-frequency thresholds for TCBCIs as compared with DCBCIs; however, little data exist examining the direct effect of skin thickness on the cochlear input signal using TCBCIs. Methods: Using seven cadaveric heads, P IC was measured in the scala vestibuli and tympani with fiber-optic pressure sensors concurrently with V Stap/RW/Prom via laser Doppler vibrometry. Ipsilateral titanium implant fixtures were placed and connected to either a DCBCI or a TCBCI. Soft tissue flaps with varying thicknesses (no flap and 3, 6, and 9 mm) were placed successively between the magnetic plate and sound processor magnet. A bone conduction transducer coupled to custom software provided pure-tone stimuli between 120 and 10, 240 Hz. Results: Stimulation via the DCBCI produced the largest response magnitudes. The TCBCI showed similar P SV/ST and V Stap/RW/Prom with no intervening flap and a frequency-dependent nonlinear reduction of magnitude with increasing flap thickness. Phase shows a comparable dependence on transmission delay as the acoustic baseline, and the slope steepens at higher frequencies as flap thickness increases, suggesting a longer group delay. Conclusion: Proper soft tissue management is critical to optimize the cochlear input signal. The skin thickness–related effects on cochlear response magnitudes should be taken into account when selecting patients for a TCBCI.